The Socioeconomic Profile of Coconut Farmers in Sei Kepayang Tengah Village Asahan Regency (Analysis of Education, Housing and Income) - Budi Rahmah Panjaitan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Coconut farmers play a crucial role in Indonesia’s rural economy. Therefore, understanding their socioeconomic conditions is vital for developing appropriate development strategies. This study examines the socioeconomic conditions of coconut farmers in Sei Kepayang Tengah Village, Asahan Regency, North Sumatra. It is hoped that the research results will become empirical evidence that can be used by the local government to develop programs that pay attention to the natural resource potential of coconut plantations in Sei Kepayang Tengah—stage—at the same time, the socioeconomic conditions of coconut farmers are a vital consideration in development planning and local economic development. In 2020, the research involved 65 households as samples out of 434 Sei Kepayang Tengah Village households. The research variables include education, housing conditions, and income. Data collection was carried out through interviews and analyzed descriptively. The results indicate that most coconut farmers have a secondary education and good housing conditions, but their income generally falls below the Regional Minimum Wage.